Effectiveness of a rock phosphate solubilizing fungus to increase soil solution phosphate impaired by the soil phosphate sorption capacity (2015)
Available phosphate (P) deficiency in tropical soils has been recognized as a major factor that limits soil quality and plant performance. To overcome this, it is necessary to add high amounts of soluble P-fertilizers; however, this is inefficient and costly. Alternatively, rock phosphates (RP) can be used, but their low reactivity limits their use. Phosphate solubilizing microorganisms (PSM) can enhance RP dissolution and, thus, improve the RP agronomic effectiveness as fertilizer. Nonetheless, their effectiveness may be impaired by the soil P fixation capacity. An experiment was carried out to assess the in vitro effectiveness of the fungus Mortierella sp. to dissolve RP in an axenic culture medium and, thus, enhance the solution P concentration in the presence of aliquots of soils with contrasting P fixation capacity. The results showed that the fungus was capable of lowering the medium pH from 7.7 to 3.0 and, thus, dissolving the RP. The presence of soil aliquots in the medium controlled the effectiveness of the fungus to increase the concentration of the soluble P. In the presence of soils with a low or medium P sorption capacity, the concentration of the soluble P was high (63.8-146.6 mg L-1) in comparison with the inoculated (soilless) treatment (50.0 mg L-1) and the uninoculated control (0.7 mg L-1). By contrast, with very-high P fixing soil aliquots, the concentration of the soluble P was very low (3.6-33.1 mg L-1); in addition, in these soils, the fungus immobilized more P into its mycelia than in soils with a low or medium P fixation capacity. The capacity of a soil to fix P seems to be a good predictor for the effectiveness of this fungus to increase the soluble P concentration via RP dissolution.